2021
DOI: 10.3390/ijms22041551
|View full text |Cite
|
Sign up to set email alerts
|

Treating Prostate Cancer by Antibody–Drug Conjugates

Abstract: Prostate cancer is the most frequent malignancy in the worldwide male population; it is also one of the most common among all the leading cancer-related death causes. In the last two decades, the therapeutic scenario of metastatic castration-resistant prostate cancer has been enriched by the use of chemotherapy and androgen receptor signaling inhibitors (ARSI) and, more recently, by immunotherapy and poly(ADP–ribose) polymerase (PARP) inhibitors. At the same time, several trials have shown the survival benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 73 publications
(42 reference statements)
0
32
0
Order By: Relevance
“…Our tumor‐tissue gene profiles showed that the autologous tumor response was represented by STEAP1, PSMA1, and PAP. Both PSMA1 and STEAP1 were previously associated with a poor prognosis, and they were considered promising targets for immunotherapy in PC 21,23,24 . PAP, the target for sipuleucel‐T, was recently shown to play a role in the development of bone metastasis in PC 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Our tumor‐tissue gene profiles showed that the autologous tumor response was represented by STEAP1, PSMA1, and PAP. Both PSMA1 and STEAP1 were previously associated with a poor prognosis, and they were considered promising targets for immunotherapy in PC 21,23,24 . PAP, the target for sipuleucel‐T, was recently shown to play a role in the development of bone metastasis in PC 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The preclinical and clinical data that drove these ADCs to their regulatory approvals have been published recently by our team [1]. In addition to these indications, many other solid malignancies, including prostate cancer [121], gastric cancer [122], pancreatic cancer [123], and hepatocellular carcinoma [124] have been entered into the focus. Table 2 presents some late-stage trials on currently non-approved oncological ADCs.…”
Section: Applications Of Adcs For Oncological and Non-oncological Conditionsmentioning
confidence: 99%
“…Results from early phase studies of PSMAtargeted ADCs have demonstrated some activity, albeit modest. 64 • MLN2704 includes a humanized J591 antibody linked to the payload maytansinoid-1.…”
Section: Antibody Drug Conjugatesmentioning
confidence: 99%